Acclimation of photosynthetic properties in psychrophilic diatom isolates under different light intensities - Ikeya, Tohru; Kashino, Yasuhiro; Kudoh, Sakae; Imura, Satoshi; Watanabe, Kentaro; Fukuchi, Mitsuo (National Institute of Polar Research, 2000)
P(論文) Acclimation of growth and photosynthetic properties was examined for diatom strains, isolated from Saroma Ko lagoon (44°N, 144°E) in early spring, under different light intensities at 1℃. The relatively high specific growth constants under low irradiances were recognized for both Chaetoceros sp. and Thalassiosira sp. Further examination of photosynthesis in Chaetoceros sp. showed that growth under low irradiance caused an increase in the photosynthetic effciency for Chl α-specific rate of gross O_2 evolution (α^B) and a decrease in the Chl α-specific rate of dark O_2 respiration (R_d^B), which was extrapolated from the initial slope of net O_2 evolution rate vs. irradiance curve. These changes explain the low light compensation point for net photosynthetic O_2 evolution (I_c) and the high efficiency for growth under low irradiance conditions. Neither Chl α-specific amounts of light-harvesting pigments, such as fucoxanthin and Chl c, nor cellular content of Chl α, but Chl α-specific amount of diadinoxanthin was varied by the change in irradiance condition. The increase of α^B under low growth irradiance corresponded with a decrease in the amount of diadinoxanthin relative to Chl α. However, the Chl α-specific maximum photosynthetic rate (P_m^B) was retained at the same level and photoinhibition could not be observed under illumination up to ∿800μE m^<-2> s^<-1>. The light intensity at which photosynthesis was light-saturated (I_k, =P_m^B/α^B) was much higher than the incident growth irradiances (76 and 88μE m^<-2> s^<-1> under the growth irradiances of 11 and 42 μE m^<-2> s^<-1>, respectively), although the value of I_k for the former was significantly smaller (t-test, P<0.001) than that for the latter. Thus, the capacity of photochemical reaction around photosystems seems to remain large even under low irradiance. These properties may indicate that the diatom cells could efficiently utilize light-energy under large variation of irradiance even on a short time-scale. ...